AKTIVITAS FISIK TERHADAP KUALITAS HIDUP PADA LANSIA: AKTIVITAS FISIK TERHADAP KUALITAS HIDUP PADA LANSIA - Ariyanto, Andry; Puspitasari Cinta, Nurwahida; Nur Utami, Dinda (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2020)
The elderly are identical with various declines in health status, especially physical health status. Physical activities are activities that cause an increase in the use of body's calorie energy. Health status of the elderly decreases along with age will affect their life quality. The more independent and often the elderly do physical activities, the higher their quality life. Objectives: This research aimed to determine the relationship between physical activities and elderly's life quality in Posyandu (Integrated Health Post) Seyegan region, Sleman. Method: This research is an observational study, which used cross sectional time approach that means all 45 subjects in Posyandu Seyegan region, Sleman using the questionnaire. Results: The results of the study with the Spearman Rank test from measurements of physical activities and life quality are p = 0.000 (p <0.05), mean there is a relationship between physical activities and elderly's life quality.